Loan Repayment and Default among Beneficiaries of Bank of Agriculture (BOA) Loan Scheme in Ogun State, Nigeria - Akerele, Ezekiel Olaoluwa; Ayodele, John Olukayode (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018DO - 10.58709/kiujss.v4i2.351.243-252, 2018)
This study focused on analysis of loan repayment and default among beneficiaries of Bank of Agriculture (BOA) loan scheme in Ogun State. The three zones of the bank operation were sampled using multistage sampling techniques. Primary and secondary data were utilized for the study and obtained with the use of a well structured questionnaire from 109 sampled respondents. Both descriptive and inferential statistics were used to analyze the data collected in line with the study objectives. The results obtained on the socio-economic characteristics of the beneficiaries revealed that majority of them were male (58.7%), age less than 50 years (75.2) with an average age of 42.51 years per beneficiary, married (75.2%), had household size of 5 (mean) per household, literate with vast majority (98.2%)  possessing one form of formal education or the other (71.6%), engaged in farming as main occupation had an average of 5 years of farming experience and (64.2%) practiced Christianity as religion. The factors that examine the reasons for loan default and the rate of default among the beneficiaries of the BOA loan revealed that the majority of the respondents considered poor weather condition (96.3%), late disbursement of loan (93.6%), marketing problems (92.7%), delay in loan approval (86.2%), short repayment period (71.6%), lack of business advisory services (63.3%) and high interest rates (57.8%) as the reasons for loan default in the BOA loan scheme. The three highest-rated reasons were poor weather condition, late loan disbursement and marketing problems. By implication, if all these factors are addressed, approval process like delayed loans approval, and late disbursement of loan, would be improved upon, it shall in turn reduce the default rate of the Bank. The findings obtained from the field also revealed that 5% of the loans disbursed suffered default in the study area. An evaluation of the factors that determined the amount of loan obtained revealed that age, education, farm size, amount repaid, past records and annual net income are the important factors determining the loan amount obtained from the Bank. In terms of constraints to the BOA loan acquisition, high interest rate, bureaucracy and inability to provide a guarantor were adjudged as the major constraints to loan acquisition in the Bank of Agriculture in Ogun State. Keywords: Loan Scheme, Repayment, Default, Interest Rate, Acquisition.